Influence of furnace type in the crystallization of lithium disilicate on bond strength and flexural strength - Karla Zancope; Thácio de Castro; Lucas do Nascimento Tavares; Marcel Santana Prudente; Flávio Domingues das Neves (Universidade Estadual de Campinas, 2019)
Aim: The crystallization step is required for lithium disilicate ceramics to change color, improve the mechanical properties and yield material to support mouth loading. Several furnaces could complete the crystallization process. This study evaluated the flexural and bond strength of lithium disilicate ceramics crystallized by different furnaces with the presence or not of vacum and different holding time. Methods: Forty lithium disilicate samples were divided into two groups: Programat P300 - control group with vacuum and holding time 7 minutes (CG) and FVPlus- experimental group and without vacuum and holding time 25 minutes (EG) and submitted to 2 experimental tests: 3-point flexural strength test and micro shear bond strength test (µSBS). For this test, the surface of the samples was treated and 1mm² of resin cement was applied on the surface. The samples were stored in artificial saliva over 2 time periods (24 hours: T0; 1-month storage: T1). To analyze the morphologic crystals of the ceramics tested, one representative specimen from each group were analyzed by using Scanning Electron Microscopy (SEM). Results: There was no significant difference in 3-point flexural strength test between groups CG and EG (p= 0.984). The µSBS results showed no statistical difference between groups, considering different storage time. There was no difference in the 3-point flexural strength and μSBS for lithium disilicate samples regardless of heat treatment of furnace type. The storage time had no influence on the μSBS. No differences were noted in the shape and size of these crystals when comparing the furnace analyzed by SEM images. Conclusion: Different furnaces did not influence the flexural and bond strength of lithium disilicate ceramics.